MicroRNA‐200a: A stage‐dependent biomarker and predictor of steatosis and liver cell injury in human immunodeficiency virus patients. Issue 1 (February 2017) - Austermann, Christian; Schierwagen, Robert; Mohr, Raphael; Anadol, Evrim; Klein, Sabine; Pohlmann, Alessandra; Jansen, Christian; Strassburg, Christian P.; Schwarze‐Zander, Carolynne; Boesecke, Christoph; Rockstroh, Jürgen K.; Odenthal, Margarete; et al.
Abstract : Nonalcoholic fatty liver disease contributes to liver‐related mortality and has a high prevalence among patients with human immunodeficiency virus (HIV). The early detection of steatosis could prevent disease progression through life‐style changes. However, as the common serum markers are nonspecific and the gold standard for the detection of nonalcoholic fatty liver disease remains the invasive liver biopsy, its verification is limited. Therefore, the search for novel biomarkers is essential. Several studies have emphasized the role of microRNAs (miRNAs) as biomarkers for certain liver diseases. With our study, we aimed to investigate the potential of miR‐200a as a biomarker for liver injury, fibrosis, and steatosis in HIV patients. The study cohort consisted of 89 HIV patients. Clinical and laboratory parameters were assessed twice, within a median follow‐up period of 12 months. miR‐200a serum levels were determined by real‐time polymerase chain reaction and normalized to spiked‐in RNA (SV40). miR‐200a serum levels showed a significant correlation with the patients' controlled attenuation parameter scores and their body weight at baseline and with alanine aminotransferase serum levels at follow‐up. At baseline, we observed a stage‐dependent increase in miR‐200a serum levels according to the degree of steatosis. More importantly, patients with higher baseline levels of miR‐200a recorded a progression of steatosis at follow‐up. Remarkably, miR‐200a not only reveals a prognostic value for steatosis but possibly also for liver damage and metabolic adaptions as patients with an increase in alanine aminotransferase/aspartate aminotransferase serum levels over time also recorded higher baseline miR‐200a levels. Conclusion : Our study reveals miR‐200a not only to be a stage‐dependent biomarker of steatosis but also to be a predictor of steatosis progression and probably liver cell injury in HIV patients. (Hepatology Communications 2017;1:36–45)